Off-Pump Triple Coronary Artery Bypass Grafting in a Patient with Situs Inversus Totalis: Case Presentation and a Brief Review of the Brazilian and the International Experiences - Karigyo,Carlos Junior Toshiyuki (2016)
Abstract A 76-year-old man with situs inversus totalis underwent a successful off-pump three-vessel coronary artery bypass surgery. The postoperative course was uneventful, and the patient was discharged 8 days later. At 9-month follow-up a coronary computed tomography angiography confirmed the viability of all of the grafts, and one year after the operation the patient remained asymptomatic. It comprises the fifth Brazilian case of a coronary surgery in a patient with situs inversus totalis and the first one of the country of a coronary artery bypass surgery without the use of the cardiopulmonary bypass in this condition.